Impact of surgical technique and analgesia on clinical outcomes after lung transplantation: A STROBE-compliant cohort study. Issue 46 (13th November 2020) - Giménez-Milà, Marc; Videla, Sebastián; Pallarés, Natalia; Sabaté, Antoni; Parmar, Jasvir; Catarino, Pedro; Tosh, Will; Rafiq, Muhammad Umar; Nalpon, Jacinta; Valchanov, Kamen
Abstract : Abstract: There is paucity of data on the impact of surgical incision and analgesia on relevant outcomes. A retrospective STROBE-compliant cohort study was performed between July 2007 and August 2017 of patients undergoing lung transplantation. Gender, age, indication for lung transplantation, and the 3 types of surgical access (Thoracotomy (T), Sternotomy (S), and Clamshell (C)) were used, as well as 2 analgesic techniques: epidural and intravenous opioids. Outcome variables were: pain scores; postoperative hemorrhage in the first 24 hours, duration of mechanical ventilation, and length of stay at intensive care unit (ICU). Three hundred forty-one patients were identified. Thoracotomy was associated with higher pain scores than Sternotomy (OR 1.66, 95% CI: 1.01; 2.74, P : .045) and no differences were found between Clamshell and Sternotomy incision. The median blood loss was 800 mL [interquartile range (IQR): 500; 1238], thoracotomy patients had 500 mL [325; 818] ( P < .001). Median durations of mechanical ventilation in Thoracotomy, Sternotomy, and Clamshell groups were 19 [11; 37] hours, 34 [IQR 16; 57.5] hours, and 27 [IQR 15; 50.5] hours respectively. Thoracotomy group were discharged earlier from ICU ( P < .001). Thoracotomy access produces less postoperative hemorrhage, duration of mechanical ventilation, and lower length of stay in ICU, but higher pain scores and need for epidural analgesia.